Identification and functional characterization of the natural variant MRP3-Arg1297His of human multidrug resistance protein 3 (MRP3/ABCC3) - Lee, Young-Min Anna; König, Jörg; Risch, Angela; Drings, Peter; Bartsch, Helmut; Keppler, Dietrich; Nies, Anne (Pharmacogenetics and genomics, 2004)
The human multidrug resistance protein 3 (MRP3, symbol ABCC3) is an ATP-binding cassette transporter that mediates the efflux of organic anions, including lipophilic substances conjugated with glucuronate, sulphate or glutathione, across the basolateral membrane of polarized cells (e.g. hepatocytes) into blood. Genetic variants of MRP3 may affect the transport of these substances out of cells. The aims of this study were: (i) to identify MRP3 polymorphisms; (ii) to functionally characterize one relatively frequent MRP3 polymorphism; and (iii) to establish whether MRP3 transports bilirubin glucuronosides. Exonic nucleotide variants in the ABCC3 gene were identified by single-strand conformation polymorphism analysis. The 3890G>A mutation, resulting in MRP3-Arg1297His, was introduced into the ABCC3 cDNA which was stably transfected into MDCKII cells. For the functional characterization of MRP3-Arg1297His in comparison with MRP3, ATP-dependent transport was analysed in isolated membrane vesicles. Two non-synonymous MRP3 variants were identified with an allele frequency of 0.003 for 1643T>A (MRP3-Leu548Gln) and 0.08 for 3890G>A (MRP3-Arg1297His). Because of the high frequency of the 3890G>A mutation, and because of the close proximity of Arg1297 to the second nucleotide-binding domain, we pursued the functional characterization of the MRP3-Arg1297His polymorphic variant. MRP3-Arg1297His was correctly localized to the basolateral membrane of polarized MDCKII cells. We identified monoglucuronosyl bilirubin, bisglucuronosyl bilirubin and leukotriene C4 as substrates for both MRP3 and MRP3-Arg1297His. Dehydroepiandrosterone-3-sulphate and 17β-glucuronosyl oestradiol were transported with similar kinetics by MRP3 and MRP3-Arg1297His. This experimental setup provides a useful tool to analyse the functional consequences of polymorphic variants of MRP3.
Im Titel ist "1297" hochgestellt
Gesehen am 11.12.2020